(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop interactive multimedia using Articulate Storyline in the subject of social sciences for grade V of elementary school, especially as a solution to the lack of learning media used in the teaching and learning process. This study uses a Research & Development (R&D) approach with the ADDIE development model which includes five stages, namely analysis, design, development, implementation, and evaluation. The data collected includes qualitative and quantitative data. The results of the study showed that the average validation score by material experts was 4.91 with the category of "very valid". Validation by media expert 1 obtained an average score of 4.77 with the category of "very valid", and media expert 2 gave an average value of 4.51 which is included in the category of "very valid". Furthermore, the practicality test conducted on 15 students produced an average value of 4.9 which is included in the category of "very practical". Finally, an effectiveness test was carried out with an average N-Gain score of 66.67% which is included in the category of "Quite Effective". Based on these results, interactive multimedia using Articulate Storyline in the subject of Social Sciences for grade V of elementary school is declared feasible to be used in the learning process